Analisis Rasio Keuangan dalam Memprediksi Perubahan Laba (Management Analysis Journal, 2015)
The purpose of this study is to know whether the CR, TAT, DR and ROA affect to profit changes. Sampling technique used in this research is purposive sampling with criteria manufacturing company listed in Indonesia Stock Exchange in 2010 to 2013 was acquired 59 sample companies. The data in the study comes from the secondary data obtained through the documentation technique. Data analysis with multiple regression analysis using SPSS for Windows version 17. Based on the result hypothesis test, then the conclusion that CR and DR has positive and significant effect in profit changes. TAT has no effect on the changes in profit changes. ROA has negative and significant effect in profit changes